Effects of cage vs. net-floor mixed rearing system on goose spleen histomorphology and gene expression profiles - Chen, Qingliang; Song, Yang; He, Zhiyu; Yang, Guang; Wang, Junqi; Li, Xiaopeng; Wang, Wanxia; Yuan, Xin; Hu, Jiwei; He, Hua; Li, Liang; Wang, Jiwen; et al. (Frontiers in Veterinary Science, 2024)
Due to the demands for both environmental protection and modernization of the goose industry in China, the traditional goose waterside rearing systems have been gradually transitioning to the modern intensive dryland rearing ones, such as the net-floor mixed rearing system (MRS) and cage rearing system (CRS). However, the goose immune responses to different dryland rearing systems remain poorly understood. This study aimed to investigate and compare the age-dependent effects of MRS and CRS on the splenic histomorphological characteristics and immune-related genes expression profiles among three economically important goose breeds, including Sichuan White goose (SW), Gang goose (GE), and Landes goose (LD). Morphological analysis revealed that the splenic weight and organ index of SW were higher under CRS than under MRS (P < 0.05). Histological observations showed that for SW and LD, the splenic corpuscle diameter and area as well as trabecular artery diameter were larger under MRS than under CRS at 30 or 43 weeks of age (P < 0.05), while the splenic red pulp area of GE was larger under CRS than under MRS at 43 weeks of age (P < 0.05).2 Besides, at 43 weeks of age, higher mRNA expression levels of NGF, SPI1, and VEGFA in spleens of SW were observed under MRS than under CRS (P < 0.05), while higher levels of HSPA2 and NGF in spleens of LD were observed under MRS than under CRS (P < 0.05). For GE, there were higher mRNA expression levels of MYD88 in spleens under CRS at 30 weeks of age (P < 0.05). Moreover, our correlation analysis showed that there appeared to be more pronounced positive associations between the splenic histological parameters and expression levels of several key immune-related genes under MRS than under CRS. Therefore, it is speculated that the geese reared under MRS might exhibit enhanced immune functions than those under CRS, particularly for SW and LD. Although these phenotypic differences are assumed to be associated with the age-dependent differential expression profiles of HSPA2, MYD88, NGF, SPI1, and VEGFA in the goose spleen, the underlying regulatory mechanisms await further investigations.